2010
DOI: 10.1007/s11244-010-9490-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment on the Selective Photocatalytic Oxidation of Benzyl Alcohol into Benzaldehyde by O2 on TiO2 Under Visible Light

Abstract: The photocatalytic oxidation of benzyl alcohol into benzaldehyde proceeded with high conversion and selectivity on a TiO 2 photocatalyst by O 2 under visible light irradiation. Surface complex formed by the interaction of benzyl alcohol with the Ti sites and/or surface OH groups of TiO 2 play an important role in the absorption of visible light and unique selective photocatalytic reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 26 publications
6
39
0
Order By: Relevance
“…Therefore, the development of visible-light-sensitive TiO 2 photocatalyst has been a great concern for efficient utilization of solar light [6][7][8][9]. Visible-light-responsive TiO 2 photocatalysts have been designed by several methods such as doping with nitrogen and other elements [10][11][12][13][14], organic dye sensitizer [15], plasmonic Au and Ag nanoparticles [16][17][18][19], and interfacial surface complexes (ISC) [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the development of visible-light-sensitive TiO 2 photocatalyst has been a great concern for efficient utilization of solar light [6][7][8][9]. Visible-light-responsive TiO 2 photocatalysts have been designed by several methods such as doping with nitrogen and other elements [10][11][12][13][14], organic dye sensitizer [15], plasmonic Au and Ag nanoparticles [16][17][18][19], and interfacial surface complexes (ISC) [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attention has been paid to photocatalysis due to the ISC formed by the interaction of TiO 2 surface with such colorless organic compounds as aromatic alcohols [20][21][22][23][24][25], amine [26,27], and phenolic compounds [28][29][30]. We previously reported the selective photocatalytic oxidation of benzyl alcohol into benzaldehyde with high selectivity on TiO 2 under visible-light irradiation [20][21][22][23][24] and theoretical studies on its reaction mechanisms by DFT calculations [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the selective photocatalytic oxidation of alcohols by O 2 under UV-light and/or visible-light irradiation on such photocatalyst as pure TiO 2 [8][9][10][11][12][13][14], dye-sensitized TiO 2 [15], gold nano-particles supported TiO 2 or CeO 2 [16,17], Fe 3+ or Rh 3+ ions modified TiO 2 [18,19], nitrogendoped TiO 2 [20], Nb 2 O 5 [21,22] and carbon nitride (C 3 N 4 ) [23] have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Augugliaro et al performed the selective photocatalytic oxidation of benzyl alcohol in pure water by using different TiO 2 samples, obtaining selectivities to benzaldehyde up to 38%. Higashimoto et al reported the selective photocatalytic oxidation of benzyl alcohol to benzaldehyde with conversion and selectivity higher than 99% on TiO 2 in the presence of O 2 under visible light irradiation using acetonitrile as solvent. Feng and co‐authors have shown that the photocatalytic selective oxidation of benzyl alcohol can be achieved over transition metal‐modified TiO 2 in the presence of molecular oxygen in a solvent free system and under ultraviolet irradiation.…”
Section: Introductionmentioning
confidence: 99%